Complex for research of efficiency of light sources with the different spectrum proceeding from heartbeart dynamics - Серобаба, Алексей Александрович (Eastern-European Journal of Enterprise Technologies, 2012)
In article the principle of creation of a complex for research of influence of light sources with a different spectrum on vegetative nervous system is described. The need of the registration of the given factor is caused by raising requirements under the registration of physiological and psychological influence of light on a human body.